STUDI LITERATUR ANALISIS PENGARUH KEPADATAN PENGGUNA TERHADAP RSRP, SINR, THROUGHPUT PADA JARINGAN 5G DI AREA URBAN - Nurwahid Fil Qodri; Yulindon Yulindon (Kampus Akademik Publiser, 2026)
The rapid development of cellular communication technology demands networks with high capacity, low latency, and optimal service quality, particularly in urban areas with high user density. 5G networks have emerged as a solution to meet these demands by offering improved speed and network efficiency. However, the performance of 5G networks is still influenced by the number of users connected within a cell. The main parameters used to measure network quality include Reference Signal Received Power (RSRP), Signal to Interference plus Noise Ratio (SINR), and throughput. This study aims to analyze the effect of user density on these three parameters in 5G networks in urban areas. The research method used is a qualitative approach through a literature review by examining various relevant scientific journals, conference proceedings, and academic publications. Data collection was conducted through documentation study, while data analysis employed a descriptive qualitative method. The results show that user density has different impacts on each network parameter. RSRP tends to remain stable and is more influenced by environmental factors, while SINR decreases due to increased interference. Throughput is the most affected parameter due to the sharing of network resources. Overall, an increase in user density leads to a decline in the quality of 5G networks in urban areas.